Factors Associated with Creativity and Innovation among Undergraduate Nursing Students - Thomas, Deena Clare; Nain, Rose A; Arsat, Norkiah; Kumilau, Raynee; Joanes, Renie Martha; Fauziningtyas, Rista; Rachmawati, Praba Diyan (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Creativity and innovation are essential competencies in nursing education, as they support problem-solving, critical thinking, and adaptability in dynamic healthcare environments. However, limited evidence exists on factors associated with creativity and innovation among undergraduate nursing students.Purpose: This study aimed to examine the association between selected sociodemographic and academic characteristics (age, gender, cumulative grade point average [CGPA], year of study, and exposure to creativity- and innovation-related courses) and creativity and innovation among undergraduate nursing students.Methods: This cross-sectional study was conducted among undergraduate nursing students at a public university in Malaysia. Using total sampling, 167 students were included. Data were collected using a structured questionnaire. Descriptive statistics were used to summarise the variables. Pearson correlation, independent t-test, and one-way ANOVA were performed to examine associations, with significance set at p < 0.05.Results: A total of 167 undergraduate nursing students were included. The mean total creativity and innovation score was 27.56 (SD = 0.79). Male students and those who had attended creativity- and innovation-related courses had significantly higher scores (p = 0.007 and p < 0.001, respectively). Creativity and innovation scores were positively correlated with CGPA (r = 0.188, p = 0.015) and negatively correlated with age (r = -0.162, p = 0.036), with no significant difference by year of study (p = 0.872).Conclusion: Creativity and innovation among undergraduate nursing students were significantly associated with gender, attendance in creativity- and innovation-related courses, CGPA, and age, but not with year of study. These findings suggest that both academic performance and educational exposure may play a role in shaping creativity and innovation competency, underscoring the importance of supportive learning experiences in nursing education.